Dimensions of political conflict and party positions in multi-level democracies: evidence from the Local Manifesto Project. Issue 1 (2nd January 2020) - Gross, Martin; Jankowski, Michael
Abstract: Partisan conflicts have been frequently analysed in comparative political science research. Yet little is known about the dimensions of political conflict at the local level in multi-level democracies. This article contributes to the literature on the estimation and analysis of party positions by first presenting a new dataset of more than 800 local party manifestos in Germany that allows for a systematic analysis of the dimensions of political conflict at the German local level. Secondly, it is demonstrated that (semi-)automatic content analysis of these texts offers a promising approach for gaining new insights into local party positions. Thirdly, the empirical analysis of German local party manifestos shows that partisan conflicts are not only structured along the left–right dimension but also along a dimension which distinguishes between parties addressing 'local' and 'national' issues to a varying degree in their manifestos, due to the different behaviour of established and populist parties.